Changing sector? Social mobility among female migrants in care and cleaning sector in Spain and Sweden. (11th September 2017) - Sánchez-Domínguez, María; Fahlén, Susanne
Abstract: This paper analyses female migrant worker's labour mobility in Spain and Sweden by using data from the Spanish National Immigrant Survey 2007 (NIS) and the Swedish Level of Living Survey for foreign-born and their children 2010 (LNU-UFB). We examine to what extent the different institutional contexts promote or obstruct the labour mobility of immigrant women in the two countries with different migration and employment regimes. First, to identify different patterns of economic integration, we analyse the labour market entry among women who started in the care and cleaning sector, in which female migrants have acquired a special role in both countries. Secondly, we investigate what factors influences sector mobility among female migrants who started in care/cleaning jobs, and the mobility into this sector. The results show that the entry into the labour market is faster in Spain than in Sweden, and that the ethnic niche of the care/cleaning sector is more evident in Spain. The results also suggest that upward mobility (from care/cleaning job sector into professional/clerk jobs) is more feasible for migrant women in Sweden, especially if they have required country-specific human capital, and that migrant women in Spain are more likely to move into the care/cleaning job sector (regardless of education and region of origin), which reflect the higher demand for care/cleaning workers in Spain. We conclude that the two institutional contexts shape opportunities for upward and lateral mobility differently for migrant women depending on their educational level and region of origin.